Comparison of frequency of urinary problems after caesarean section and instrumental vaginal delivery - Naz, Tabassum; Benish, Benish; Khushboo, Khushboo; Waheeda, Waheeda; Shamas Din Lakho, Samreen (Journal of Neonatal Surgery, 2025)
Objective: The Objective Of The Study Was: To Determine Frequency Of Post-Partum Urinary Complications Among Women To Compare Frequency Of Urinary Problems (Ppvd, Uti And Urinary Incontinence) Following Caesarean Section And Instrumental Vaginal Delivery. Study Design: A Cross-Sectional Study Setting: Study Was Conducted In Obstetrics And Gynaecology Department, Shaikh Zayed Women Hospital, Larkana. Duration Of Study: Six Months After The Approval Of Synopsis. (13-01-2020 To 12-07-2020) Sampling Technique: Non- Probability Consecutive Sampling Methodology:All The Female Patients Of Age 18-45 Years Undergoing Delivery Of Fetus Either Through Caesarean Section Or Instrumental Vaginal Delivery And With Any Parity Or Gravidity Were Included. Written Informed Consent For Inclusion In The Study Was Taken From Each Patient. Appropriate Evaluation Was Done In All The Cases And Name, Age, Body Mass Index (Bmi), Gravidity And Parity Was Obtained. Patients Were Divided Into Two Groups. Patients In Group A Were Those Undergoing Cesarean Section While Patients In Group B Were Those Undergoing Instrumental Vaginal Delivery. Mode Of Delivery Was Decided As Per Obstetrical Merits As Decide By Consultant Obstetrician. All The Patients In Both Groups Were Looked In The Follow Up Clinic For Urinary Problems ((Ppvd, Uti And Urinary Incontinence)). All Data Was Analyzed Using Spss Version 24. Results: A Total Of 138 Patients Were Included In The Study. The Mean Age Of The Patients Was Found To Be 30.73 ± 7.33 Years. Patients Were Further Categorized According To Age Groups Into 2 Groups And Most Were In The Age Range Of 31-45 Years. Also, Most Of The Patients Had Parity ≤3. The Mean Parity Was 2.85 ± 2.07. The Mean Bmi Of Patients Was Found As 29.89 ± 4.20 Kg/M2. Regarding Gravidity, Mean Gravidity Was 4.38 ± 2.21. Most Of The Patients Had Undergone Ivd. The Most Common Urinary Problem Seen Was Ppvd (N=29), Followed By Urinary Incontinence And Uti. Also, Stratification Of Urinary Problems With Respect To Age, Parity, Bmi And Gravidity Was Done. Conclusion:Urinary Complications Were Frequently Higher Among Our Patients Who Had Undergone Pregnancy And Childbirth. Therefore, We Suggest That We Need To Educate Our Patients Regarding These Complications And Take Certain Measures To Prevent Them.